2021
DOI: 10.1017/s1537592721002036
|View full text |Cite
|
Sign up to set email alerts
|

The Pandemic Policy U-Turn: Partisanship, Public Health, and Race in Decisions to Ease COVID-19 Social Distancing Policies in the United States

Abstract: We explore the US states’ evolving policy responses to the COVID-19 pandemic by examining governors’ decisions to begin easing five types of social distancing policies after the initial case surge in March–April 2020. Applying event history models to original data on state COVID-19 policies, we test the relative influence of health, economic, and political considerations on their decisions. We find no evidence that differences in state economic conditions influenced when governors began easing. Governors of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 55 publications
(52 reference statements)
0
9
0
Order By: Relevance
“…For example, researchers have found differences in steps taken by states to manage the pandemic are influenced by political partisanship (Makridis and Rothwell, 2020), and Hardy (2020) found those who identified as right-wing were less likely to believe it was necessary to engage in recommended hygiene practices. Additionally, Ye (2021) and Adolph et al (2021) found differences by county and state in vaccination rates and the lifting of stay-at-home orders.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…For example, researchers have found differences in steps taken by states to manage the pandemic are influenced by political partisanship (Makridis and Rothwell, 2020), and Hardy (2020) found those who identified as right-wing were less likely to believe it was necessary to engage in recommended hygiene practices. Additionally, Ye (2021) and Adolph et al (2021) found differences by county and state in vaccination rates and the lifting of stay-at-home orders.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, some states, like Massachusetts, had limits on the number of people who could gather at one time, while others had no such restrictions (Kaiser Family Foundation, 2020). Some states varied the types of business that could open while others had blanket orders that covered all business types (like restaurants and gyms) (Adolph et al, 2021). One of the explanations for widely different responses by state is political affiliation of the leaders, especially the state's Governor who were the ones making policies.…”
Section: Refusals and The Revelation Risk Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Rather than adding an arbitrary positive quantity to these count variables, we directly estimate the effect of having zero children (or zero health facilities) by including dummy variables in the model to indicate cases where each is precisely zero. In turn, and without loss of generality, before logging the count of health facilities (or children), we replaced zeros with ones, so that cases in which there are zero health facilities within 20 km (or no children under 5 years of age) affect the outcome only through the dummy variable for that case 31 32…”
Section: Methodsmentioning
confidence: 99%